Can the Number of Correlation Coefficient (R Value) as a Statistical Indicator of Metal-Polluted Ecosystem? A Comparison between Polluted and Unpolluted Ecosystems - C. K. Yap (Institute of Advanced Engineering and Science, 2013)
The present paper is the first in the literature to present evidence that correlation coefficient (r value) can be used as a potential indicator of metal-polluted sediments collected from polluted and unpolluted ecosystems which were also supported by a few reported studies. Based on the correlation analysis on the heavy metals in the surface sediments, collected from two contrasting ecosystems, polluted and unpolluted areas, it was evidently found that the polluted ecosystems had higher numbers of significant correlation coefficients (P< 0.05) than the unpolluted ones. This could be due to the fact that the polluted ecosystems had wider ranges of values of heavy metal concentrations due to some elevated levels of metals recorded. Therefore, the correlation coefficients (r values) can be used as potential indicators for the polluted ecosystems. However, cautions should be exercised in which the monitoring studies should be able to truly reflect the overall environmental quality of the ecosystem, ranging from effluent-receiving point sources to the clean sites far away from the sources. However, further investigations are still necessary before number of significant r values can be confidently employed as indicator of metal-polluted ecosystem.